A cautionary note: False homozygosity for BRCA2 6174delT mutation resulting from a single nucleotide polymorphism masking the wt allele - Solano, Angela Rosario (2002)
Sequencing an amplification product of the terminal segment of BRCA2 exon 11 showed apparent homozygosity for the 6174delT mutation in two healthy sisters. Subsequent sequencing of an alternate overlapping amplicon revealed the presence of the 5972C>T polymorphism, which is within the standard upstream amplification primer. This mismatch was responsible for the failure to amplify the normal (5972T) allele in both sisters who were heterozygous for the 6174delT mutation. Though the unexpected finding of apparent homozygosity for the 6174delT mutation prompted re-evaluation of the assay, the potential for false negative results due to masking of a mutation-bearing allele by such a circumstance should be a cautionary note for the testing and also in the interpretation of the results published under such assay conditions.